The Effect of Yoga on Reducing Stress and Improving CD4 Counts among People with HIV: A Systematic Review and Meta-Analysis - Hidayat, Jufri; Chen, Miao-Yen; Pranata, Satriya (Jurnal Keperawatan Soedirman, 2023)
Stress is a common mental health problem among HIV patients. Yoga has been frequently used to manage stress, but its potential benefits are not well-established yet. The aim of this meta-analysis is to assess the effect of yoga intervention on reducing stress and improving CD4 among HIV populations. Electronic bibliographic databases were systematically searched for articles reporting randomized controlled trials on yoga, HIV, and stress. The inclusion criteria were studies that (a) assessed yoga intervention in HIV patients; (b) included control groups; (c) evaluated psychological stress or biomarkers of stress as the outcome; and (d) provided mean and standard deviation scores for both groups to calculate the effect size. Meanwhile, our exclusion criteria were studies that (a) used other than randomized controlled trial design; (b) were written in a language other than English; and (c) included participants other than HIV patients. Six studies were sampled, with a total of 348 participants that met our criteria. HIV positive participants who received yoga interventions reported significantly reduced psychological stress compared to control group (total effect size was -0.85, with 95% CI from -1.47 ~ -0.23). Thus, yoga is a stress management exercise that health care providers can use to treat HIV patients.